1993
DOI: 10.1007/bf00151869
|View full text |Cite
|
Sign up to set email alerts
|

Methods for animal cell immobilization using electrostatic droplet generation

Abstract: A technique for the production of small polymer microbeads (less than 150 pm diam.) utilizing electrostatic spraying is presented. Video and image analysis were performed to reveal details of the mechanism of droplet formation. Microbeads coated with poly-L-lysine were prepared and found to be effective as microcarriers for culturing surface immobilized insect cells to a high cell density (1.55 x lo7 cells/ml microbeads).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Hommel et al (1988) proposed replacing the continuous voltage by very short pulses (1 to 6 ms) with a controlled frequency (10 to lOO/s) in order to obtain beads in the range of 100 to 200 pm. Bugarski et al (1993) demonstrated alginate microbead production (450 pm) by electrostatic spraying. In this case, pulsed voltage was not necessary.…”
Section: Extrusion Under Electrostatic Potentialmentioning
confidence: 99%
“…Hommel et al (1988) proposed replacing the continuous voltage by very short pulses (1 to 6 ms) with a controlled frequency (10 to lOO/s) in order to obtain beads in the range of 100 to 200 pm. Bugarski et al (1993) demonstrated alginate microbead production (450 pm) by electrostatic spraying. In this case, pulsed voltage was not necessary.…”
Section: Extrusion Under Electrostatic Potentialmentioning
confidence: 99%
“…Electrostatic extrusion is a novel, proven technique for immobilization of various cell types, such as brewing yeast cells (Nedovic et al 2001a, 2001b, 2002), insect cells (Bugarski et al 1993, 1994), and plant cells (Sajc et al 1995). The advantages of electrostatic extrusion make the technique a first choice for immobilization procedures in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Few attempts though have been made in the application of electric fields to the production of micron-sized polymer beads for cell immobilization . In recent articles (Bugarski et al, 1993(Bugarski et al, , 1994a, the mechanism of droplet formation using an electrostatic droplet generator was investigated with a variable-voltage power supply. Animal cell suspensions were successfully extruded using the electrostatic droplet generator.…”
Section: Introductionmentioning
confidence: 99%